Vestibuloplasty using Diode Laser: A Case Report - Subedi, Suraksha; Ranjit, Rebicca; Bista, Soni (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Inadequate vestibular depth causes deficiency in width of keratinised gingiva which ultimately results in poor plaque control and difficulty in maintenance. Vestibuloplasty is a novel procedure for managing shallow vestibular depth and can be achieved with scalpel, electrocautery, cryosurgery, or laser. With the recent advancements in dentistry, laser therapy has gained popularity over conventional modalities as it is effective yet non-invasive procedure. Among various lasers available, diode lasers are extensively used in oral soft tissue surgery. This case report describes the management of a shallow vestibule using diode laser.